The impact of Malta's tapering of benefits scheme on employment - Kurt Sant (Central Bank of Malta, 2023)
Before 2014, Malta's labour market policy took a passive approach. However, in 2014 government made a paradigm shift through several Active Labour Market Policies aimed at 'Making Work Pay'. This article analyses the Tapering of Benefits (TOB) scheme, aimed at unlocking the poverty trap stalemate and led to stable employment for Unemployment Assistance (UA), Social Assistance (SA) and Single Unmarried Parents (SUP) beneficiaries. Its introduction coincided with a sharp drop in registered beneficiaries. Survival analysis and Cox proportional hazard models are employed to analyse the impact that the scheme had on the job-finding rate amongst such beneficiaries. Secondly, this paper analyses the impact on the chances of successfully retaining employment once individuals previously on benefits find a job. These analyses are based on high-quality national data on the whole population of beneficiaries and their employment history in Malta. Results show that the TOB doubles the job-finding probability, with SUP and SA beneficiaries enjoying the scheme the most and the least, respectively. The impact declines with age and has no gender effect. The chance of job termination drops by 11.8 pp for eligible individuals. Furthermore, its impact once the scheme ends is not different from the first 36 months, showing that its impact is robust in the medium term.
Keywords: 330